Industrial Training Report : Jabatan Pembangunan Persekutuan Kelantan (JPPK) / Nur Syuhada Mat Husin - Mat Husin, Nur Syuhada (Faculty of Information Management, 2018)
Industrial Training is a compulsory requirement for all students at Universiti Teknologi Mara (UiTM ) as a requirement for graduating as well as a subject in this semester. Therefore, this report will explain about Nur Syuhada Binti Mat Husin (2015145595) industrial training at Jabatan Pembangunan Persekutuan Negeri Kelantan which is located Jalan Tengku Petra Semerak, Kota Bharu, Kelantan Darul Nairn. It also intends to explain about the daily routine done and all tasks given during the session. The training session starts from 1st February 2018 until 28th Jun 2018.